The Quran Manuscripts in Indonesia: A Historical Review - Kuswandi, Dedi; Rohman, Abdul; Muttaqien, Ghazi Abdullah (Universitas Muhammadiyah Surakarta, 2024)
Codicology, the study of written manuscripts, plays a vital role in understanding the history of human civilization, particularly in the context of the development and preservation of Quranic manuscripts. The Nusantara region, which includes Indonesia and parts of Malaysia, boasts a rich tradition of Quranic manuscript production and copying. This research seeks to explore the codicological history of Quranic manuscripts in the Nusantara, focusing on their origins, evolution, regional differences, and significance in the religious and cultural lives of Muslim communities in the area. The research methodology includes analyzing various historical sources, such as existing Quranic manuscripts, historical records, academic studies, and other primary materials. The data collected is examined to identify patterns, trends, and regional distinctions. The findings reveal that the codicological history of Quranic manuscripts in the Nusantara mirrors the region's cultural diversity and the deep-rooted Islamic traditions. These manuscripts originate from various regions and showcase a wide range of writing styles, decorative elements, and materials, shaped by influences such as cultural interactions, technological progress, and local preferences. Understanding this history better can contribute to preserving the cultural and religious heritage of the Nusantara and enhance knowledge of Islamic civilization in the region.